National Estimates of Emergency Department Visits for Antibiotic Adverse Events Among Adults—United States, 2011–2015 - Geller, Andrew I. (J Gen Intern Med, 2018)
BACKGROUND: Detailed, nationally representative data describing high-risk populations and circumstances involved in antibiotic adverse events (AEs) can inform approaches to prevention. OBJECTIVE: Describe US burden, rates, and characteristics of emergency department (ED) visits by adults for antibiotic AEs. DESIGN: Nationally representative, public health surveillance of adverse drug events (National Electronic Injury Surveillance System-Cooperative Adverse Drug Event Surveillance [NEISS-CADES]) and a nationally projected database of dispensed prescriptions (QuintilesIMS), 2011–2015. PATIENTS: Antibiotic-treated adults (≥ 20 years) seeking ED care. MAIN MEASURES: Estimated annual numbers and rates of ED visits for antibiotic AEs among outpatients treated with systemically administered antibiotics. KEY RESULTS: Based on 10,225 cases, US adults aged ≥ 20 years made an estimated 145,490 (95% confidence interval, 115,279–175,701) ED visits for antibiotic AEs each year in 2011–2015. Antibiotics were implicated in 13.7% (12.3–15.2%) of all estimated adult ED visits for adverse drug events. Most (56.6%; 54.8–58.4%) antibiotic AE visits involved adults aged < 50 years, and 71.8% (70.4–73.1%) involved females. Accounting for prescriptions dispensed from retail and long-term care pharmacies, adults aged 20–34 years had twice the estimated rate of ED visits for oral antibiotic AEs compared with those aged ≥ 65 years (9.7 [7.6–11.8] versus 4.6 [3.6–5.7] visits per 10,000 dispensed prescriptions, respectively). Allergic reactions accounted for three quarters (74.3%; 70.0–78.6%) of estimated ED visits for antibiotic AEs. The three most frequently implicated antibiotic classes in ED visits for antibiotic AEs were oral sulfonamides (23.2%; 20.6–25.8%), penicillins (20.8%; 19.3–22.4%), and quinolones (15.7%; 14.2–17.1%). Per-prescription rates declined with increasing age group. CONCLUSIONS: Antibiotics are a common cause of ED visits by adults for adverse drug events and represent an important safety issue. Quantifying risks of AEs from specific antibiotics for specific patient populations, such as younger adults, provides additional information to help clinicians assess risks versus benefits when making the decision to prescribe or not prescribe an antibiotic. AE rates may also facilitate communication with patients about antibiotic risks. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-018-4430-x) contains supplementary material, which is available to authorized users.